New media and transformation of social life in China - Wu, Xinxun; Zheng, Han; Wu, Xiaokun (Los Angeles, CA : SAGE Publications, Inc., 2018)
The field of media and communication has expanded substantially in China over the last few decades. New Media and the Transformations of Social Life in China covers in detail the main aspects related to media in China, including new media technologies, social networks, media convergence, smart cities, digital media, information and communication technology (ICT), and risk society. A major strength of this book is its coverage of the role of ICT for social participation in urban policy and management areas, which include e-governance, social security, and decision support systems. The book also addresses issues such as the financial crisis, the global energy crisis, and environmental pollution.
Description based on XML content.
Includes bibliographical references.
Keywords: Mass media -- Social aspects -- China -- History -- 20th century; Mass media -- Social aspects -- China -- History -- 21st century